Senior life quality in Pardubice - Liedermanová, Ivana (Univerzita Pardubice, 2010)
The contribution is based on current demographics of aging, not only in Europe, but also in the Czech Republic. It is necessary to investigate both economical and social impacts in context of individual policies and to implement them into upcoming conceptions. Within the frame of the community plan of social and related services, The City of Pardubice has a concept of work with seniors that will be changing with respect to the results of the upcoming research.
Keywords: seniors; process of ageing; social work; social care; community planning; life quality; demographic development